Information ethics - Córdoba González, Saray (2005)
The use of information is an unavoidable activity in today's world, but for such effects the condition of access is imposed so that the use is possible and equitable. Hence, the author presents the concept of information ethics, to later refer to free access to information as a means to contribute to the democratization of knowledge and finally refers to intellectual property.